2013
DOI: 10.1111/bioe.12023
|View full text |Cite
|
Sign up to set email alerts
|

Bioethics Methods in the Ethical, Legal, and Social Implications of the Human Genome Project Literature

Abstract: While bioethics as a field has concerned itself with methodological issues since the early years, there has been no systematic examination of how ethics is incorporated into research on the Ethical, Legal and Social Implications (ELSI) of the Human Genome Project. Yet ELSI research may bear a particular burden of investigating and substantiating its methods given public funding, an explicitly cross-disciplinary approach, and the perceived significance of adequate responsiveness to advances in genomics. We unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…In order to ensure that the appropriate ELSI research is conducted to answer these myriad questions, ELSI researchers must ensure adequate understanding of scientific facts and possibilities of gene editing, ensure appropriate use of robust methods [ 29 ] to answer specific ELSI questions, as well as learn from previous research on related themes such as (traditional) gene therapy, reproductive technologies, and GMOs. Furthermore, funding will have to be prioritized for ELSI research.…”
Section: Ongoing Reflection Research and Dialogue On The Elsi Of Genmentioning
confidence: 99%
“…In order to ensure that the appropriate ELSI research is conducted to answer these myriad questions, ELSI researchers must ensure adequate understanding of scientific facts and possibilities of gene editing, ensure appropriate use of robust methods [ 29 ] to answer specific ELSI questions, as well as learn from previous research on related themes such as (traditional) gene therapy, reproductive technologies, and GMOs. Furthermore, funding will have to be prioritized for ELSI research.…”
Section: Ongoing Reflection Research and Dialogue On The Elsi Of Genmentioning
confidence: 99%
“…In this respect, RRI re-focuses technological governance from standard debates on risks to discussions about the ethical stewardship of innovation" (Schroeder and Ladikas, 2015 [156]).  "A transparent, interactive process by which societal actors and innovators become mutually responsive to each other with a view to the (ethical) acceptability, sustainability and social desirability of the innovation process and its marketable products (in order to allow a proper embedding and technological advances in our society)" (von Schomberg, 2013 [159]).…”
Section: Box 52 Understandings Of "Responsible Research and Innovatmentioning
confidence: 99%
“…Unlike much of classical bioethics, large consortia ELSI naturally trends more toward the practical implications of scientific research, often with the goal of providing pertinent research and relevant commentary regarding the extrascientific concerns of a particular area of scientific research. Working with the consortia of Big Science, ELSI researchers are often more able than their social science peers to be practical, providing prescriptive real-time analysis, and, for example, providing for the identification of downstream contentious issues before an overly zealous implementation of the science becomes particularly problematic (Walker and Morrissey 2014). Some have suggested that the Genetic Information Nondiscrimination Act of 2008 (GINA), which prohibits genetic-based discrimination by employers and health insurers, is a direct outgrowth of ELSI research in the area of genomic privacy (Shen 2013).…”
Section: Elsi Associated With Consortia Science May Be More Practicalmentioning
confidence: 99%